Follicular fluid total antioxidant capacity levels in PCOS. (3rd July 2016) - Yilmaz, Nafiye; Inal, Hasan Ali; Gorkem, Umit; Sargin Oruc, Ayla; Yilmaz, Saynur; Turkkani, Ayten
Abstract : In this study, our aim was to assess total antioxidant capacity (TAC) levels in follicular fluid (FF) and their relationship to clinical pregnancy rates in PCOS patients undergoing assisted reproduction (ART). Twenty-two women with polycystic ovary syndrome (PCOS) (Group 1) and 41 women without PCOS (Group 2) were included in this study. Clinical and laboratory parameters and FF TAC levels were investigated. No statistically significant differences were found between the groups with regard to age and baseline parameters. Although we could not demonstrate a significant difference in FF TAC levels between the two groups ( p =0.469), there was a significant positive correlation between FF TAC and clinical pregnancy rates, BMI, and the duration of infertility for the entire group ( r =0.254, p =0.048; r =0.312, p =0.013; r =0.259, p =0.040; respectively). Owing to the correlation between FF TAC and the clinical pregnancy rates, further studies evaluating the impact of FF TAC levels on ART outcomes in patients with PCOS and other etiologies of infertility are needed.